2017
DOI: 10.3389/fphys.2017.00170
|View full text |Cite
|
Sign up to set email alerts
|

Elastase-2, a Tissue Alternative Pathway for Angiotensin II Generation, Plays a Role in Circulatory Sympathovagal Balance in Mice

Abstract: In vitro and ex vivo experiments indicate that elastase-2 (ELA-2), a chymotrypsin-serine protease elastase family member 2A, is an alternative pathway for angiotensin II (Ang II) generation. However, the role played by ELA-2 in vivo is unclear. We examined ELA-2 knockout (ELA-2KO) mice compared to wild-type (WT) mice and determined whether ELA-2 played a role in hemodynamics [arterial pressure (AP) and heart rate (HR)], cardiocirculatory sympathovagal balance and baroreflex sensitivity. The variability of syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Echocardiography was performed in two distinct groups of mice, around 30 days after ligature, with a Vevo 2100 High-Resolution Imaging System (Visual Sonics, Toronto, ON, Canada), using a 30-MHz transducer. The steps and procedures were performed as previously described 32 . Briefly, mice were slightly anaesthetized using 1.5% isoflurane in 100% oxygen.…”
Section: Symbolic Analysis Of Hrvmentioning
confidence: 99%
“…Echocardiography was performed in two distinct groups of mice, around 30 days after ligature, with a Vevo 2100 High-Resolution Imaging System (Visual Sonics, Toronto, ON, Canada), using a 30-MHz transducer. The steps and procedures were performed as previously described 32 . Briefly, mice were slightly anaesthetized using 1.5% isoflurane in 100% oxygen.…”
Section: Symbolic Analysis Of Hrvmentioning
confidence: 99%
“…A previous study showed that ELA-2 KO promotes reduction in HR, changing the sympathovagal balance in mice and enhances the parasympathetic activity without affecting BP ( 11 ). ACE inhibition in ELA-2 KO mice caused a significant decrease in BP ( Figure 2 ) as expected, probably due to the withdrawal of two important routes of ANG II production.…”
Section: Discussionmentioning
confidence: 99%
“…ELA-2 knockout (ELA-2 KO) mice presented a lower heart rate (HR) compared with their wild-type counterparts. This strain shows changes in the autonomic balance, displaying increased parasympathetic flow, possibly due to the reduction of ANG II concentrations ( 11 ). However, the participation of ACE on the autonomic and hemodynamic profile of ELA-2 KO mice is still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Animals: adult male and female ELA2KO (38 males/27 females) or C57BL6/j (33 males/33 females) mice, used as wild-type controls (WT), from 12-16 weeks of age at the beginning of the experiments, were employed. The ELA2KO were developed in the Max Delbrück Center for Molecular Medicine, Berlin, Germany; and the colony expanded in the Department of Physiology, at the University of São Paulo in Ribeirão Preto [21]. The animals were group housed, with free access to food and water, except during experimental sessions.…”
Section: Methodsmentioning
confidence: 99%